2013
DOI: 10.1002/ajpa.22324
|View full text |Cite
|
Sign up to set email alerts
|

Sex estimation based on deciduous and permanent dentition in a contemporary spanish population

Abstract: Sex estimation of skeletal remains with satisfactory allocation accuracy represents an essential step in reconstructing the biological profile of unknown individuals in archaeological research and forensic practice. Teeth are among the most frequently recovered physical elements of an individual that remain after death due to their hardness, durability, and resistance to postmortem insults. This study was based on the deciduous and permanent dentition of 269 individuals (150 males and 119 females) from the Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 54 publications
13
70
1
6
Order By: Relevance
“…A comparison between the two sexes showed that the classification accuracy of all functions was higher for males. This result is in agreement with other studies on cervical tooth measurements (Vodanovic et al 2007;Hassett 2011;Viciano et al 2011Viciano et al , 2013Viciano et al , 2015Zorba et al 2011Zorba et al , 2013Mujib et al 2014;Peckmann et al 2015). This means that females have a greater variation in tooth size and can more often be misclassified as male.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A comparison between the two sexes showed that the classification accuracy of all functions was higher for males. This result is in agreement with other studies on cervical tooth measurements (Vodanovic et al 2007;Hassett 2011;Viciano et al 2011Viciano et al , 2013Viciano et al , 2015Zorba et al 2011Zorba et al , 2013Mujib et al 2014;Peckmann et al 2015). This means that females have a greater variation in tooth size and can more often be misclassified as male.…”
Section: Discussionsupporting
confidence: 94%
“…Discriminant function analysis for single tooth measurements also showed that the cervical measurements of the permanent canines and incisors were the most dimorphic teeth providing classification accuracy between 76.9 and 87.9 %. These results were in accordance with previous studies (Alt et al 1998;Starp 1990;Ellendt 1993;Hassett 2011;Viciano et al 2011Viciano et al , 2013Viciano et al , 2015Mujib et al 2014). In addition, it was found that second molar dimensions can be a very effective single variable for sex estimation with a classification accuracy of 83 %.…”
Section: Discussionsupporting
confidence: 94%
“…A comparison between the two sexes showed that the classification accuracy of all functions was higher for males. This result is in agreement with other studies on molar odontometrics [13,[17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…The correct identification of sex from skeletal remains is one of the main challenges in forensic anthropology and osteoarchaeology. Dental sexual dimorphism has long been acknowledged as a reliable biological feature in this respect, and studies have demonstrated that dental dimensions can be used to accurately assess the sex of skeletal remains in different populations [1][2][3][4][5][17][18][19][20][21][22][23][24]. The present study is one of few reference studies for sex estimation using odontometric data in Iranian archaeological populations [7].…”
Section: Resultsmentioning
confidence: 86%
“…Esto ha favorecido el empleo de métodos para establecer el sexo y la edad de los individuos más aproximativos que los convencionales. La determinación de la edad para los subadultos sigue a Ubelaker (1978) y Schaefer et al (2009), para la estimación del sexo en adultos a Viciano et al (2013) y Alemán et al (1997) y para la edad a Işcan et al (1984Işcan et al ( , 1985 y Brothwell (1989). El conjunto consta de un mínimo de 19 sujetos (Tab.…”
Section: Restos óSeos Humanos Y Cronologíaunclassified